2011
DOI: 10.1128/jvi.05091-11
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Species Analysis of the Replication Complex of Old World Arenaviruses Reveals Two Nucleoprotein Sites Involved in L Protein Function

Abstract: Lassa virus (LASV) causing hemorrhagic Lassa fever in West Africa, Mopeia virus (MOPV) from EastAfrica, and lymphocytic choriomeningitis virus (LCMV) are the main representatives of the Old World arenaviruses. Little is known about how the components of the arenavirus replication machinery, i.e., the genome, nucleoprotein (NP), and L protein, interact. In addition, it is unknown whether these components can function across species boundaries. We established minireplicon systems for MOPV and LCMV in analogy to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 43 publications
3
32
0
Order By: Relevance
“…Although NP is not essential for the catalytic activity of L itself ( Fig. 1), it is likely that NP is critical for activities not recapitulated by the initial steps of RNA synthesis initiation in vitro, including integrity of the full-length genome and possibly reduction of RNA secondary structure (29,30). Here we demonstrate that Z is a direct modulator of the viral RNA synthesis machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Although NP is not essential for the catalytic activity of L itself ( Fig. 1), it is likely that NP is critical for activities not recapitulated by the initial steps of RNA synthesis initiation in vitro, including integrity of the full-length genome and possibly reduction of RNA secondary structure (29,30). Here we demonstrate that Z is a direct modulator of the viral RNA synthesis machinery.…”
Section: Discussionmentioning
confidence: 99%
“…To date there is no direct evidence of reassortant bunyaviruses emerging due to co-infection in an animal. As for arenaviruses, despite reassortment occurring in vitro , the risk of recombining segments is low, possibly due to superinfection exclusion; and as yet no natural reassortants have been detected for the arenaviruses3940. The current study shows that viral transmission was not detected between NHP groups infected with segmented viruses of the same family (RVF/CCHFV and LASV/MACV) therefore minimizing the possibility for reassortment.…”
Section: Discussionmentioning
confidence: 59%
“…Intriguingly, a previous study reported coimmunoprecipitation (co-IP) of L-NP in the absence of arenavirus-specific RNA with the use of a vaccinia virus system (MVAT7pol)-based expression system for L and NP (21). These apparently conflicting findings can be explained considering that the MVA-T7pol-based expression system results in hyperphysiological levels of L and NP that may overcome the requirement for virus-specific RNA.…”
Section: Mg Igrmentioning
confidence: 56%